Does ownership structure moderate the relationship between systemic risk and corporate governance? Evidence from Gulf Cooperation Council countries - Ilyes Abidi; Mariem Nsaibi; Khaled Hussainey (Journal of Risk and Financial Management, 2022)
The objective of this paper is to empirically examine the moderating effect of ownership structure on the relationship between systemic risk and corporate governance. It complements prior research by studying the relationship between the proportion of capital held by state institutions and systemic risk. It also examines the internal governance mechanisms that mitigate systemic risk. For this purpose, this research used a dataset consisting of 22 banks from Gulf Cooperation Council (GCC) countries (10 Islamic banks and 12 conventional banks) over the period 2004-2018. We used a three-stage least squares (3SLS) regression to test our research hypotheses. The findings revealed that the structure of the board of directors (BOD) reduced systemic risk in the banking sector. In particular, we provide evidence that board composition and board meetings negatively affect systematic risk. In addition, we provide empirical evidence that the state plays a key role in moderating the relationship between governance mechanisms and systemic risk. As such, our paper provides significant contributions to the governance and corporate finance literature.
Keywords: G21; G32; G28; 650; systemic risk; corporate governance; ownership structure